THE EFFECT OF PHARMACOTHERAPY ON THE QUALITY OF LIFE OF PREGNANT WOMEN WITH ARTERIAL HYPERTENSION - Kamolova Diyora Djamshedovna; Khusainova Munira Alisherovna; Ergasheva Ma’mura Tashtemirovna; Uzokov Jurabek Bakhtiyorovich (Scholar Express Journals, 2023)
However, women, due to their biological and social characteristics, also have problems specific to them related to their reproductive function. In this regard, the question cannot but arise on the definition and study of the quality of life of pregnant women. Despite the short duration and transience of the pregnancy period in a woman's life, it is at this time that she is most exposed to adverse physical, psychological, and social factors, which determines the change in the quality of her life. Arterial hypertension (AH) during pregnancy more than 20 years ago was characterized by the World Health Organization as one of the most important international medical problems. The frequency of hypertensive conditions in pregnant women in different regions of Russia ranges from 7 to 29%
Keywords: arterial hypertension; pregnant woman; quality of life